Towards More-Than-Human Negotiation - Paula Palanco Lopez; Anna Krzywoszynska; Agnese Bankovska (Suomen Antropologi)
Scholars from all disciplines are becoming increasingly conscious of the co-dependence between humans and more-than-humans. This special collection engages these debates, guided by a question both practical and theoretical: What makes good relationships between humans and nonhumans in societies under strain? The essays collected in this issue explore this question through different cases of more-than-human relationality. In this introduction, we briefly present these contributions, placing them in dialogue with the concept of the contact zone. The contact zone, we argue, provides a powerful conceptual tool for thinking about the how as well as the why in human–more-than-human encounters, as it highlights the materiality and constructedness of more-than-human affects and ethics. Thus, the first part of this introduction highlights how the different contributions to the special issue further the conceptual work ushered by the concept of the contact zone. Furthermore, we make a contribution to the growing literature on more-than-human contact zones by drawing attention to the tensions and frictions that necessarily appear within these. What may be helpful in understanding and navigating these tensions, we argue, is the concept of more than-human negotiation. We believe that this ecological view of contact zones opens up an exciting new arena for more-than-human research.